PERILAKU BULLYING YANG MENYIMPANG DARI PANCASILA SEBAGAI IDEOLOGI SISWA PAUD - Ester Sianipar; Hanisa Yesilistiawati; Rachel Sehulina; Sherina Ayu Viana; Sherly Mardini; Jamaludin Jamaludin (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
There have been many cases of bullying in this country involving early childhood, it can even be said that bullying behavior is an act that deviates from the ideological values ​​of Pancasila. This study aims to determine the meaning, impact, distribution and ways to deal with bullying, this research uses a case study approach on the basis of theory, impact, distribution and ways to overcome bullying. Researchers suggest that teachers can be responsive or responsive to bullying behavior in PAUD. This research will also examine how to handle bullying cases. Keywords: Bullying, Pancasila Ideological Values, Early Childhood Education